2023
DOI: 10.1042/bst20221300
|View full text |Cite
|
Sign up to set email alerts
|

The emerging roles of autophagy in intestinal epithelial cells and its links to inflammatory bowel disease

Abstract: Landmark genome-wide association studies (GWAS) identified that mutations in autophagy genes correlated with inflammatory bowel disease (IBD), a heterogenous disease characterised by prolonged inflammation of the gastrointestinal tract, that can reduce a person's quality of life. Autophagy, the delivery of intracellular components to the lysosome for degradation, is a critical cellular housekeeping process that removes damaged proteins and turns over organelles, recycling their amino acids and other constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 139 publications
2
2
0
Order By: Relevance
“…The connection between endocytic trafficking and intestinal physiology has not been widely researched. Our data here characterizing Atg7 intestinal epithelial-specific knock-out mice are consistent with published roles of autophagy in the intestinal epithelium, where a loss of autophagy conjugation proteins including ATG5, ATG16 and ATG7, results in Paneth and goblet cell defects, minimally affects enterocytes, and mice do not develop enteritis unless a chemical or pathogenic agent is administered 1 , 14 . Interestingly, we did not observe apoptosis and loss of intestinal stem cells in our ATG7-deficient mice, as reported in Trentesaux et al 11 , but this is potentially due to our assessment of mice at a much earlier time point.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The connection between endocytic trafficking and intestinal physiology has not been widely researched. Our data here characterizing Atg7 intestinal epithelial-specific knock-out mice are consistent with published roles of autophagy in the intestinal epithelium, where a loss of autophagy conjugation proteins including ATG5, ATG16 and ATG7, results in Paneth and goblet cell defects, minimally affects enterocytes, and mice do not develop enteritis unless a chemical or pathogenic agent is administered 1 , 14 . Interestingly, we did not observe apoptosis and loss of intestinal stem cells in our ATG7-deficient mice, as reported in Trentesaux et al 11 , but this is potentially due to our assessment of mice at a much earlier time point.…”
Section: Discussionsupporting
confidence: 88%
“…It encapsulates cytoplasmic material within autophagosomes and mediates their delivery to the lysosome for degradation. Critically, genome-wide association studies (GWAS) have identified that polymorphisms in genes that regulate autophagy correlate with a susceptibility to inflammatory bowel disease (IBD), which includes Crohn’s disease and ulcerative colitis 1 . Subsequent studies aiming to understand this connection between autophagy and intestinal health led to the generation of mice deficient for, or bearing, disease variants in autophagy regulators.…”
Section: Introductionmentioning
confidence: 99%
“…The connection between endocytic trafficking and intestinal physiology has not been widely researched. Our data here characterising Atg7 intestinal epithelial-specific knock-out mice are consistent with published roles of autophagy in the intestinal epithelium, where a loss of autophagy conjugation proteins including ATG5, ATG16 and ATG7, results in Paneth and goblet cell defects, minimally affects enterocytes, and mice do not develop enteritis unless a chemical or pathogenic agent is administered 1,22 . Interestingly, we did not observe apoptosis and loss of intestinal stem cells in our ATG7-deficient mice, as reported in Trentesaux et al 11 , but this is potentially due to our assessment of mice at a much earlier time point.…”
Section: Discussionsupporting
confidence: 88%
“…Several studies have shown that amino acids from poultry feed trigger protein synthesis during epithelial cell proliferation [ 64 66 ]. Moreover, protein content is responsible for epithelial cell regeneration and signal transduction in the small intestine [ 67 ], thus enhancing the efficiency of nutrient absorption [ 68 ]. In addition, flavonoid content plays a major role in antibacterial activity and stimulates epithelial cells to undergo mitosis.…”
Section: Discussionmentioning
confidence: 99%